2020
DOI: 10.2174/1573401315666190206142929
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Essential Oils of Echinops spinosus and Carlina vulgaris Rich in Polyacetylene Compounds

Abstract: Background: The essential oils of aromatic plants are increasingly used as new biocontrol alternative agents against microbial strains and insect pests of fruits and vegetables, because of their specificity of biodegradable nature. Objective: This work, treats for the first time the chemical composition, antioxidant, antifungal and insecticidal activities of the essential oils obtained from Echinops spinosus and Carlina vulgaris from Algeria. Methods: The chemical compositions of oils were investigated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Some studies on the antibacterial and antifungal properties of this plant have been reported, showing promising activities not only against K. pneumoniae and E. coli [ 13 ], but also against S. pyogenes and P. aeruginosa [ 14 ]. This plant was also reported to be effective against some fungal strains, such as P. expansum and A. niger [ 11 ], C. albicans , and C. glabrata [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on the antibacterial and antifungal properties of this plant have been reported, showing promising activities not only against K. pneumoniae and E. coli [ 13 ], but also against S. pyogenes and P. aeruginosa [ 14 ]. This plant was also reported to be effective against some fungal strains, such as P. expansum and A. niger [ 11 ], C. albicans , and C. glabrata [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies report the activity of this plant against different microorganisms. For instance, Kernóczi et al [ 10 ] reported a moderate activity against some Gram-positive bacteria, while Belabbes et al [ 11 ] reported an antifungal activity of the EO against Penicillium expansum and Aspergillus niger . The antimicrobial activity of the EO and decoction obtained from the roots was also significant against Staphylococcus aureus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carlina oxide is an acetylenic compound which was isolated for the first time from Carlina accaulis by Semmler in 1902 [14] and its correct structure was proposed by Gilman van ess and Burtner in 1933 [15]. Subsequently, it has been confirmed that Carlina oxide is present in the chemical composition of several extracts and essential oils of plants belonging to the Asteraceae family, it is present mainly in the essential oil of Carlina accaulis [14][15][16], Carlina acanthifolia [17], Carlina diae [18], Carlina vulgaris [19],…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the different biological activities provided by this compound which has shown very promising antimicrobial, antitrypanosmal, anti-inflammatory, antiulcer and antioxidant activities [19][20][21][22][23][24]. On the other hand, the study by Benelli et al [25] showed that carlina oxide exhibits a certain non-selective cytotoxicity towards normal human dermis cells and tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The use of conventional insecticides has an enormous impact, boosting food production and contributing significantly to the improvement of human health, including the reduction of the onset of vector-borne diseases. , However, the misuse and overuse of insecticides led to several negative consequences such as the accumulation in food, water, and soil, the development of pesticide resistance, and nontarget effects on human health and the ecosystem. In this context, botanical insecticides represent innovative and safe alternatives to conventional products due to their promising efficacy on a wide spectrum of vectors and agricultural pests and their moderate to low impact on the environment, as well as on human and animal health. However, the limited supply of the raw material from botanical sources may lead to exploring alternative routes for obtaining these insecticidal agents. Carlina acaulis L. is a medicinal plant belonging to the Asteraceae (Compositae) family and native to the calcareous soils of southern and central Europe with documented biological activities. Its root essential oil (EO) is characterized by the predominance (>95%) of 2-(3-phenylprop-1-ynyl)­furan, commonly known as carlina oxide ( 1 ) …”
mentioning
confidence: 99%